Characterization of Synthetic Ni(II)-Xylenol Complex as a Photosensitizer for Wide-Band Gap ZnO Semiconductor Electrodes - Suman Kushwaha; Lal Bahadur (International Journal of Photoenergy, 2011)
A synthetic NiIIL(H2O)2 complex (L = xylenol orange, 3,3′-bis [N,N-di(carboxymethyl)-aminomethyl]-o-cresol sulphonapthalein (H2O)2), which is a water-soluble dye, has been studied for its photosensitizing properties at n-ZnO semiconductor electrodes prepared by sol-gel techniques. The absorption spectrum of aqueous solution of this complex exhibits a strong peak at 563 nm and a shoulder at 526 nm wavelength of light. The sandwich-type dye-sensitized solar cell using ZnO semiconducting thin film with test dye anchored onto it showed the cell output as follows: VOC=0.506 V, Jsc=1.68 mA cm−2, and FF=0.41 under illumination with full spectrum of light (intensity 520 mW cm−2), while on illumination with visible light (λ>420 nm, intensity 480 mW cm−2), VOC=0.506 V, Jsc=1.4 mA cm−2, and FF=0.49 were achieved. Maximum incident photon-to-current conversion efficiency for the present system was found to be 8.7% at wavelength (λmax=563 nm).